The moderating influence of environment factors in an extended community of inquiry model of e-learning. Issue 1 (2nd January 2021) - Lee, Richard; Hoe Looi, Kim; Faulkner, Margaret; Neale, Larry
ABSTRACT: Like their global counterparts, e-learning platforms are an indispensable technology in many Asia Pacific tertiary institutions. Despite its widespread adoption, e-learning is still being criticized as merely mirroring traditional classroom formats but in digital forms. If tertiary institutions in Asia Pacific wish to harness e-learning and be globally recognized, they need to first overcome such criticisms by understanding what drives students' satisfaction. Drawing on the community of inquiry (COI) model, this study attempts to determine the factors that underpin students' satisfaction with their e-learning experience. Surveying students from a Malaysian university, this study shows that while cognitive presence and social presence influence e-learning satisfaction directly, teaching presence is mediated by cognitive and social presence. Furthermore, two environmental factors, content quality and perceived ease-of-use, moderate the relationships among the three presences and e-learning satisfaction. We argue that this extended and more comprehensive model would help educators better understand e-learning's use as an effective pedagogical platform. We discuss the implications of the findings for higher education institutions and offer directions for future research.